Pre-treatment anemia in head and neck cancer: risk factors, subtypes, and survival outcomes - Kürten, Cornelius H. L.; Sivakumar, Vinithagowry; Waßenberg, Sebastian; Schleupner, Marie Carolin; Funk, Valentin; Lazzarini, Elena; Aksu, Sara; Guberina, Maja; Gauler, Thomas; Stuschke, Martin; Mattheis, Stefan; Lang, Stephan; et al. (Frontiers in Oncology, 2025)
IntroductionAnemia in head and neck cancer (HNC) may be due to additive, overlapping or competing causes. Here we aim to investigate the prevalence of pre-therapeutic anemia, associated risk factors, subtypes, and impact on survival among HNC patients, including the clinically relevant subgroups of HPV-associated HNC.Materials and methodsA retrospective chart review of HNC patients diagnosed between 2010 and 2020 identified a study cohort of 921 patients. Every patient was subject to pre-therapeutic laboratory testing which was correlated with clinical data and oncologic outcomes.ResultsPre-therapeutic anemia was present in 18.1% of patients with advanced age, low BMI, systemic inflammation, and kidney dysfunction being significant risk factors for anemia. For oropharyngeal cancers, p16+ status was associated with lower anemia prevalence and offset the impact of smoking history on anemia risk when compared to all HNC patients. 19.2% of patients were hypochromic-microcytic and 4.2% were hyperchromic-macrocytic, indicative of iron or vitamin B12/folate deficiency, respectively. Even mild anemia (11- 12.9 g/d) was associated with a survival disadvantage compared to non-anemic patients (64% vs. 85% overall survival, <0.001).ConclusionAnemia is a significant negative survival predictor in HNC patients, with severity affecting prognosis. A relevant subgroup of patients had potentially reversible anemia subtypes, early identification and treatment of which may improve outcomes.